104k views
2 votes
Solve for r: q = p(r + s)

User Zero
by
4.9k points

2 Answers

6 votes

Step-by-step explanation: To solve for r, start by distributing the p

through the parentheses on the left side to get q = pr + ps.

Next, isolate the r term by subtracting ps from both sides to get -ps + q = pr.

Finally, to get r by itself, divide both sides by p and we have -ps + q/p = r.

User Madrugada
by
4.8k points
3 votes

Answer:


r=(q-ps)/(p)

General Formulas and Concepts:

  • Order of Operations: BPEMDAS
  • Equality Properties
  • Distributive Property

Explanation:

Step 1: Define equation


q=p(r+s)

Step 2: Solve for r

  1. Distribute p:
    q=pr+ps
  2. Subtract ps on both sides:
    q-ps=pr
  3. Divide both sides by p:
    (q-ps)/(p) =r
  4. Rewrite:
    r=(q-ps)/(p)
User OHY
by
4.9k points